2018
DOI: 10.1002/jcp.26381
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐1290 promotes proliferation, migration, and invasion of glioma cells by targeting LHX6

Abstract: To investigate the interaction of miR-1290 and LHX6 in gliomas, and their influence on the propagation and metastasis of glioma cells. The differential expression of miR-1290 in glioma cells was identified by chip screening. The expression level of miR-1290 and LHX6 were determined by qRT-PCR and Western blot. The influence of miR-1290 on propagation of glioma cells were analyzed by MTT assay, EdU incorporation, and colony formation, while the impact of miR-1290 on metastasis was assessed by transwell assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
6
29
0
Order By: Relevance
“…Further selecting HepG2 cells with the highest expression level of miR-1290 in liver cancer cells to extract exosomes miR-1290 was carried out for subsequent tests, it was found that the proliferation, invasion, migration and epithelial-mesenchymal transformation capabilities of liver cancer cells co-cultured with exosomes miR-1290 were significantly increased, while the apoptosis capability was significantly reduced, suggesting that miR-1290 plays a role of oncogene in liver cancer, while exosomes miR-1290 could enhance its tumor activity. Looking up relevant literature, we found that Yan et al [24] were also studying the role of miR-1290 as a tumor-promoting gene in glioma, which also confirmed the consistency of the biological effects of miR-1290.…”
Section: Discussionsupporting
confidence: 73%
“…Further selecting HepG2 cells with the highest expression level of miR-1290 in liver cancer cells to extract exosomes miR-1290 was carried out for subsequent tests, it was found that the proliferation, invasion, migration and epithelial-mesenchymal transformation capabilities of liver cancer cells co-cultured with exosomes miR-1290 were significantly increased, while the apoptosis capability was significantly reduced, suggesting that miR-1290 plays a role of oncogene in liver cancer, while exosomes miR-1290 could enhance its tumor activity. Looking up relevant literature, we found that Yan et al [24] were also studying the role of miR-1290 as a tumor-promoting gene in glioma, which also confirmed the consistency of the biological effects of miR-1290.…”
Section: Discussionsupporting
confidence: 73%
“…Further selecting HepG2 cells with the highest expression level of miR-1290 in liver cancer cells to extract exosomes miR-1290 was carried out for subsequent tests, it was found that the proliferation, invasion, migration and epithelial-mesenchymal transformation capabilities of liver cancer cells co-cultured with exosomes miR-1290 were signi cantly increased, while the apoptosis capability was signi cantly reduced, suggesting that miR-1290 plays a role of oncogene in liver cancer, while exosomes miR-1290 could enhance its tumor activity. Looking up relevant literature, we found that Yan et al 24 were also studying the role of miR-1290 as a tumor-promoting gene in glioma, which also con rmed the consistency of the biological effects of miR-1290.…”
Section: Discussionsupporting
confidence: 56%
“…Among the top-regulated miRNAs was miR-210, known to respond to hypoxia and with many documented roles in cancer [23]. Here, we identified a new hypoxia-associated miRNA, miR-1290, which promotes cell migration and invasion of cancer cells [69,70]. In addition, EV miR-1290 was found to be a biomarker in ovarian carcinoma [71].…”
Section: Discussionmentioning
confidence: 87%